Concordant mast cell and basophil production by individual hematopoietic blast colony-forming cells - Metcalf, Donald (National Academy of Sciences, 2013)
Previous studies have shown that mouse bone marrow cells can produce mast cells when stimulated in vitro by stem cell factor (SCF) and interleukin-3 (IL-3). Experiments to define the marrow cells able to generate mast cells showed that the most active subpopulations were the Kit(+) Sca1(–) progenitor cell fraction and the more ancestral Kit(+) Sca1(+) blast colony-forming cell fraction. In clonal cultures, up to 64% of blast colony-forming cells were able to generate mast cells when stimulated by SCF and IL-3, and, of these, the most active were those in the CD34(–) Flt3R(–) long-term repopulating cell fraction. Basophils, identified by the monoclonal antibody mMCP-8 to mouse mast cell serine protease-8, were also produced by 50% of blast colony-forming cells with a strong concordance in the production of both cell types by individual blast colony-forming cells. Enriched populations of marrow-derived basophils were shown to generate variable numbers of mast cells after a further incubation with SCF and IL-3. The data extend the repertoire of lineage-committed cells able to be produced by multipotential hematopoietic blast colony-forming cells and show that basophils and mast cells can have common ancestral cells and that basophils can probably generate mast cells at least under defined in vitro conditions.